Perlindungan Hukum terhadap Perempunan sebagai Korban Tindak Pidana Perdagangan Manusisa (Tracfficking) ( Studi Kasus Pengadilan Negeri Medan Putusan No 1451 /PID . SUS /2021 PN Medan) - Khairul Nas; Mhd Ridawan Lubis (Inovasi Pratama Internasional. Ltd, 2023)
Formulation of the problem 1. What is the form of legal protection for women as victims of trafficking in persons 2. What are the legal actions against the perpetrators of the crime of trafficking in persons. 3 What solutions are taken by legal protection officials in overcoming obstacles to providing protection for women. The purpose of the research 1. To find out the form of legal protection for women as victims of trafficking in persons.2. To find out legal actions against perpetrators of criminal acts of trafficking in persons. To find out what solutions are taken by legal protection officials in overcoming obstacles to providing women's protection. Research Methods The author uses a normative juridical method because the target of this research is law and norms. The definition of rules includes, legal principles, rules in the narrow sense and concrete legal regulations. This normative juridical research method aims to find coherent truths through deductive ways of thinking. The deductive way of thinking means that the research will depart from a specific idea. Research Results Legal protection for victims of the crime of trafficking in persons can not only be realized in the form of punishment of the perpetrators, but also in the form of fulfilling rights, including the right to obtain confidentiality of identity, the right to to obtain restitution or compensation, as well as the right to obtain .1. Declare that the Defendant HANITA SARI NASUTION ALS NONA has been legally and convincingly proven guilty of committing the crime of “Trafficking in Persons”; 2. Sentenced punishment on the Defendant therefore with imprisonment for 4 (four) years and a fine of Rp. 120,000,000.00 (one hundred and twenty million rupiahs) provided that if the fine is not paid, it is replaced with imprisonment for 3 (three) months.. The government's efforts or solutions to overcome human trafficking are as follows. The government strengthened security at the border. The government is strengthening laws and enforcement on human trafficking. The government cooperates with other countries, especially in the investigation and prosecution of perpetrators of human trafficking.